2011
DOI: 10.1016/j.psychres.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition and experience in Huntington's disease: Is there a differential impairment?

Abstract: Findings on affective processing deficits in Huntington's disease (HD) have been inconsistent. It is still not clear whether HD patients are afflicted by specific deficits in emotion recognition and experience. We tested 28 symptomatic HD patients and presented them with pictures depicting facial expressions of emotions (Karolinska-Set) and with affective scenes (International Affective Picture System; IAPS). The faces were judged according to the displayed intensity of six basic emotions, whereas the scenes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 36 publications
6
22
0
Order By: Relevance
“…A number of previous studies, however, have found altered self-reported emotional experiences in response to visual stimuli in individuals with HD (e.g., Paradiso et al, 2008; Eddy et al, 2011; Ille et al, 2011a). Abnormal visual scanning behavior in HD may have contributed to these previous findings.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A number of previous studies, however, have found altered self-reported emotional experiences in response to visual stimuli in individuals with HD (e.g., Paradiso et al, 2008; Eddy et al, 2011; Ille et al, 2011a). Abnormal visual scanning behavior in HD may have contributed to these previous findings.…”
Section: Discussionmentioning
confidence: 86%
“…The most frequently reported deficit is an impaired ability to identify emotions from pictures of actors posing with emotional facial expressions (e.g., Sprengelmeyer et al, 1996; Johnson et al, 2007; Labuschagne et al, 2013; Bora et al, 2016). Furthermore, many studies have found alterations in the self-reported experience of emotion in response to emotionally evocative stimuli (c.f., Mitchell et al, 2005; Paradiso et al, 2008; Eddy et al, 2011; Ille et al, 2011a; De Tommaso et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found a differential impairment in others' emotion recognition and subjective emotional involvement in HD, the former being reduced and the latter enhanced in respect to controls [12].…”
Section: Introductionmentioning
confidence: 89%
“…At the best of our knowledge, this is the first study on EEG correlates of affective images in HD, while few studies evaluated valence and arousal ratings in the same patients [12]. The late positivity we evaluated in the 400-700 msec range corresponds in healthy controls to the cortical processing following the recognition and discrimination of pictures content, expressed in the 200-400 range, and it is subtended by a specific involvement of brain areas sustaining attentive processing toward motivational significance, emotional stimuli [32].…”
Section: Lpp Amplitudementioning
confidence: 99%